Proceedings of the 7th International Conference on Entrepreneurship and Business Management 2018
DOI: 10.5220/0008488200590066
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Financial Attitude, Locus of Control, and Income on Financial Behavior

Abstract: This study aims to examine the relationship between locus of control, the financial attitudes and income of workforces whom have worked and lived on Jakarta, Indonesia. The object of this researce is Financial Attitudes, Locus of Control, Financial Behaviour, and Income. The sample consisted of 395 respondents were taken through purposive sampling, the data processed using SmartPLS 3.0. This study found that there are positive effect relationship between locus of control, the financial attitudes and Financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 0 publications
0
8
1
1
Order By: Relevance
“…A study by Szendrey and Fiala (2018) found that income significantly impacted financial management behavior. However, in contrast to the study of Arifin et al (2018), income did not substantially affect financial management behavior.…”
Section: Introductioncontrasting
confidence: 85%
“…A study by Szendrey and Fiala (2018) found that income significantly impacted financial management behavior. However, in contrast to the study of Arifin et al (2018), income did not substantially affect financial management behavior.…”
Section: Introductioncontrasting
confidence: 85%
“…Numerous studies have also examined FWB and financial behaviour from the perspective of young or emerging adults. Many of these studies used university students as their sample (e.g., Shim et al, 2009 ; Falahati et al, 2012 ; Lanz et al, 2020 ), although some others used young working adults within a certain age range as respondents (e.g., Arifin et al, 2018 ; Topa et al, 2018 ; Yong et al, 2018 ). The focus on youths and young adults have continued to spur research interest among scholars since this group of the population plays an important role in society, being future leaders that would lead the world into even more challenging circumstances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The present study contributes to the literature by incorporating financial behaviour as a mediator between LOC and perceived FWB, which is scant in the literature. Past studies have usually examined the direct relationship between LOC and financial behaviour (e.g., Britt et al, 2013 ; Arifin et al, 2018 ; Parmitasari et al, 2020 ; Adiputra, 2021 ; Triono, 2021 ), the direct relationship between LOC and FWB, wellness or satisfaction ( Prawitz and Cohart, 2016 ; Adiputra, 2021 ) or the mediating effect of LOC on the relationship between certain antecedents and FWB or financial outcomes (e.g., Grable et al, 2015 ; Bulmash, 2016 ; Furnham and Cheng, 2017 ; Ullah and Yusheng, 2020 ; Peetz et al, 2021 ), which is in line with the study by She et al (2022) . However, the present study differs from She et al (2022) by including two important socio-demographic variables into the model, i.e., income and education.…”
Section: Introductionmentioning
confidence: 99%
“…The locus of control defines human psychological characteristics [72]. One of the personality traits is the locus of control, defined as an individual's belief in their ability to exert self-control or their mentality dictating their success or failure in life [73].…”
Section: Locus Of Controlmentioning
confidence: 99%
“…The higher an individual's internal locus of control, the greater their financial responsibility. This is because an individual is viewed as more capable of controlling them-self, managing finances, resisting the influence of others, being more motivated, and completing challenging tasks than those with a lower locus of control [72]. Thus, this causes a positive and negative relationship between locus of control and financial stress.…”
Section: Locus Of Controlmentioning
confidence: 99%